Suspension high velocity oxy-fuel spraying of TiO2: A quantitative approach to phase composition. Issue 2 (February 2017) - Pala, Z.; Shaw, E.; Murray, J.W.; Senin, N.; Hussain, T.
Abstract: A range of coatings from a water based suspension of anatase has been prepared by suspension high velocity oxy-fuel spraying with the aim to study effects of heat power of the flame on phase composition, microstructure and surface topography. Three most commonly used approaches of quantitative phase analysis have been scrutinized with respect to their applicability and as some of the coatings showed presence of preferred orientation and it was argued that quantitative Rietveld refinement is the most accurate method for phase composition determination. Coatings had a layered duplex anatase/rutile microstructure with fraction of rutile increasing exponentially with heat power. Spraying at the lower heat power led to a lower surface roughness and higher power resulted in surfaces with pronounced humps, which were distributed homogeneously on the surface. The emergence of humps is related to an increase in macroscopic surface area of up to 30% with respect to the flat coating.